Visual and Refractive Outcomes after Topographic-Guided Customized Ablation Photorefractive Keratectomy in Keratoconic Eyes - Mohammad Rabei, Hossein; Ghadyani , Zahra; Delfaza , Siamak; Feizi, Sepehr (Journal of Ophthalmic and Optometric Sciences, 2023)
Purpose: To investigate the visual and refractive outcomes of topographic-guided customized ablation treatment (T-CAT) photorefractive keratectomy (PRK) combined with iris registration and the use of mitomycin C among patients who have undergone corneal transplantation. Patients and Methods: This cross-sectional study was conducted on 18 eyes of 14 patients with keratoconus over a 2-year period at Torfeh Eye Hospital, Tehran, Iran. Of these patients, 11 patients were male and 3 patients were female. All participants had previously undergone penetrating keratoplasty (PKP) or deep anterior lamellar keratoplasty (DALK) and subsequently underwent T- CAT PRK surgery with 0.02 % mitomycin C to correct residual refractive errors due to intolerance or reluctance to wear glasses or contact lenses. Pre- and post- T-CAT PRK surgery assessments included uncorrected visual acuity (UCVA), best-corrected visual acuity (BCVA), cylindrical and spherical lens measurements, spherical equivalent, and corneal opacity in the transplanted cornea. Results: The mean postoperative spherical equivalent decreased from 4.27 ± 2.28 D to 1.48 ± 1.39 D, a statistically significant reduction (P = 0.001). The improvements in UCVA, BCVA, and spherocylinder levels were also statistically significant during the follow-up periods after PRK. Conclusion: The present study suggest that T-CAT PRK combined with iris registration and the use of mitomycin C intraoperatively in keratoconus patients who have undergone corneal transplantation can effectively treat spherical astigmatism. This approach significantly reduced refractive errors and improved visual and refractive parameters.